Pengembangan Modul Ajar Perencanaan Karir Berbasis Kompetensi Sosial Emosional untuk Siswa Kelas XII - Aan Soka Pardini (Kartika: Jurnal Studi Keislaman, 2026)
This study aims to develop a Social Emotional Competency-Based Future Career Planning Teaching Module for grade XII high school students that meets valid and practical criteria. This study uses the Research and Development (R&D) method with the ADDIE model which includes the stages of Analyze, Design, Development, Implementation, and Evaluation. The research subjects consisted of material and language experts, media experts, and grade XII high school students as module users. The results of the study indicate that the developed teaching module obtained a very valid category based on the assessment of material and language experts, as well as media experts, reviewed from the aspects of content feasibility, language, presentation, and graphics with a score of 96.5%. The practicality test by students showed that the teaching module was in the very practical category with a score of 93%, reviewed from ease of use, attractiveness of the display, clarity of the material, and its usefulness. Practicality testing by teachers showed a score of 94% in the very practical category. The integration of social emotional competencies in the teaching module can help students improve self-awareness, emotional management, decision-making skills, and responsibility in determining career choices. This module is declared feasible and practical for use in guidance and counseling services in high schools.